The Influence of Community Behavior on Water Quality of The Anyar River in Surakarta City Based on Physical-Chemical Parameters - Inggrid Trifena Yulia; Ilhamnul Zain Satria Negara; Snada Indah Tuk Negari; Muchammad Sholiqin; Siti Rachmawati (Diponegoro University, 2022)
The Anyar River is a tributary of the Bengawan Solo River, which is located in the city of Surakarta. The Anyar River has a watershed area of approximately 305.2 km2 and the length of the main river from the Anyar River is approximately 61.96 km. This river is important for people's lives, but the awareness of the surrounding community is still lacking, as evidenced by several community houses that there is still feces disposal from the septic tank, which is channeled directly to the Anyar River through pipes. The surrounding community did not hold any cleaning activities for the Anyar River, only a rule from the local RT not to throw garbage in the Anyar River. When the dry season arrives, the water in the Anyar River will recede and will occasionally be polluted when it is dry. These things will certainly affect the quality of the water in the Anyar River. This study aims to determine the effect of community behavior on the water quality of the Anyar River, Surakarta City, based on water physico-chemical parameters. The research method used is a descriptive qualitative method, obtained through observation and interviews as well as several journal articles related to physical and chemical parameters in water. The results of this study indicate that at the three main location points in the Anyar River, no water pollution was found based on the results of measurements of physical-chemical parameters such as pH, temperature, DO, TDS, and turbidity. However, at location point II, the branch was found to be more polluted because it was used by local residents for direct disposal. From the results of the study, it can be concluded that the awareness of citizens to maintain water quality in the Anyar River is still a bit lacking, so some recommendations are given by inviting residents to work together to clean the river; make IPAL and household water disposal (septic tank) independently; emphasize not to throw garbage in the river; and residents can take advantage of PAHs during the rainy season.